Developments and future clinical outlook of taxane nanomedicines - Louage, Benoit; De Wever, Olivier; Hennink, Wim E.; De Geest, Bruno G. (Elsevier BV, 2017)
Taxanes are highly valuable drugs for cancer treatment. Low water-solubility however puts a major challenge in obtaining formulations that are stable and easy-to-use in clinical practice. Initially, solubilization and lowering toxicity of taxanes has been the main research focus. However, emerging passive and active targeting strategies, especially in the field of nanomedicine, have been capital incentives to further broaden therapeutic index by improving efficacy. This review provides an up-to-date clinical track record of taxane nanomedicines in view of the current state-of-the-art in anti-cancer drug delivery. Additionally, the clinical status of taxane nanomedicines is discussed and considerations are provided for improving future clinical translation.
Keywords: Cancer; Conjugates; Nanomedicine; Nanoparticles; Paclitaxel; Taverne; Pharmaceutical Science; SDG 3 - Good Health and Well-being